Answer:
Step-by-step explanation:
This is of the form
[tex]P(t)=a(b)^t[/tex]
Where P(t) is the ending population, a is the original population, b is the growth rate, and t is time in years. We have everything we need to solve for t.
[tex]80000=40000(1.19)^t[/tex]
Let me explain the growth rate quickly. If the exponential function is a growth function, that means (in this particular situation) that we have 100% of the population and we are increasing it by 19%. That makes the growth rate 119%, which in decimal form is 1.19.
Begin by dividing both sides by 40000 to get
[tex]2=(1.19)^t[/tex]
To get that t out of its current exponential position, take the natural log of both sides:
[tex]ln(2)=ln(1.19)^t[/tex]
and the rules of logs say we can bring the exponent down out front:
ln(2) = t*ln(1.19)
Divide both sides by ln(1.19) to get t alone:
[tex]\frac{ln(2)}{ln(1.19)}=t[/tex]
Doing that calculation on your calculator gives you that
t = 3.9846...
but rounding to the nearest tenth gives you that
t = 4.0 years